Adsorpsi Asam Humat pada Zeolit Alam yang Dimodifikasi dengan TiO2 - Septiani, Upita; Tasari, Fiska Julian; Zilfa, Zilfa (Jurnal Riset Kimia, 2020)
This research modified natural zeolite with TiO2 synthesized by the sol-gel process which was applied as a humic acid adsorbent. The purpose of this study was to coat natural zeolites with TiO2 to increase the adsorption capacity of natural zeolites as humic acid adsorbents. The natural zeolite powders were obtained from Kabupaten Solok, West Sumatra, based on X-ray Fluorescence (XRF) analysis, the ratio of silica/alumina (Si/Al) was 4.35, indicating that natural zeolite was clinoptilolite zeolite. Scanning Electron Microscopy (SEM) analysis showed natural zeolite has a rough surface with closed pores while zeolite coated with TiO2 (zeolite/TiO2) has a homogeneous, smooth surface with open pore. The results of the Energy Dispersive X-Ray Spectroscopy (EDS) analysis showed that the level of TiO2 was 7.1%, this result showed that TiO2 has been coated on the surface of the zeolite. Natural zeolite and zeolite/TiO2 were applied as humic acid adsorbents. Maximum adsorption capacity of natural zeolites and zeolites/TiO2 were 0.2787 mg/g and 1.199 mg/g, respectively.